SYNTHESIS AND CHARACTERIZATION OF PHOTOCATALYS Fe2O3 PILLARED MONTMORILLONITE DOPED TiO2 AND ITS APPLICATION FOR RHODAMINE B PHODODEGRADATION USING VISIBLE LIGHT IRRADIATION - D. A. D. N. Dewi; I N. Simpen; I W. Suarsa (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2020)
A montmorillonite clay modified with semiconductor metal can act as a photocatalyst material. Montmorillonite clays were chosen because of their natural characteristics which are easily to be modified and have high specific surface area. This research aims to modify montmorillonite clay into photocatalyst material. The montmorillonite clay was intercalated using Fe2O3 to produce Fe2O3-pillared montmorillonite clay, then doped with TiO2 to form a photocatalyst material Fe2O3-PILC / TiO2. Modifications were intended to increase the specific surface area and number of active photocatalyst sites and thus increase the ability of photodegradation. The characterization carried out included characterizing the pillar formation using X-ray Diffraction (XRD), specific surface area by the BET method (Bruneau, Emmet, and Teller), a the number of surface acid-base sites by the titration method. Photocatalyst with the best character was Fe2O3-PILC / TiO2 1: 3 with specific surface area, number of acid and base sites respectively 45,947 m2/g, 20,1736 x 1023 sites/gram and 19,0044 x 1023 sites/gram. The result of photodegradation at optimum condition with visible light at pH 3 using 400 mg photocatalyst was 99.84%. Keywords: photocatalyst, Fe2O3, montmorillonite clay, TiO2, rhodamine B